THE STUDY OF SIMPLE SENTENCE STRUCTURE IN WORLD LINGUISTICS (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article is dedicated to the study of simple sentence structure in world linguistics. It examines the concept of a sentence as a syntactic unit that expresses a complete thought with intonational and grammatical completeness. Special attention is given to the grammatical category of predicativity, as well as to various classifications of sentences based on communicative purpose, emotionality, reality, structure, and components. The paper traces the historical development of the study of simple sentences in English grammar from the 16th–18th centuries to the structural and transformational grammars of the 20th century. It analyzes the views of prominent scholars such as J. Brightland, L. Murray, V.G. Admoni, A.I. Smirnitsky, N.P. Gaman, and O.V. Dolgova, and explores types of syntactic connections: attributive, predicative, copulative, and completive. The article concludes with the importance of syntactic-semantic approaches and the diversity of grammatical models in global linguistics when analyzing the structure of the simple sentence.